Political Economy From the Perspective of Ibn Khaldun - Muslim, Moch Bukhari; Saepullah, Saepullah; Widayatsari, Any (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2019)
The political economy encompasses the management of revenues and spending to achieve the social welfare of the community. Hence, development is not solely emphasized economic growth but also equity. This article discusses the political economy according to Ibn Khaldun, written in his book, Muqaddimah. This study concludes that that political budgets must be carried out in a balanced manner by establishing budget certainty and increasing the discipline in use of the budget. Legislators make laws, referring to the creation of income sources so that the community will be able to meet their needs independently, and the government can gather capabilities to carry out their duties and functions. Ibn Khaldun saw budget management as a means to solve public matters while also factoring the interests of rulers and governments. Ekonomi politik meliputi pengelolaan pendapatan dan pengeluaran untuk mencapai kesejahteraan sosial masyarakat. Karenanya, pembangunan adalah tidak semata-mata menekankan pertumbuhan ekonomi tetapi juga pemerataan. Artikel ini membahas tentang ekonomi politik menurut Ibnu Khaldun, ditulis dalam bukunya, Muqaddimah. Studi ini menyimpulkan bahwa anggaran politik harus dilakukan secara seimbang cara dengan menetapkan anggaran kepastian dan meningkatkan disiplin dalam penggunaan anggaran. Legislator membuat undang-undang, merujuk pada penciptaan sumber pendapatan sehingga masyarakat akan dapat memenuhi kebutuhan mereka secara mandiri, dan pemerintah dapat mengumpulkan kemampuan untuk melaksanakan tugas dan fungsinya. Ibn Khaldun melihat manajemen anggaran sebagai sarana untuk menyelesaikan masalah publik sementara juga anjak kepentingan para penguasa dan pemerintah.